DIGITIZATION OF JAVANESE MANUSCRIPTS IN THE STUDY OF ARCHIPELAGO MANUSCRIPTS AT THE REKSA PUSTAKA MANGKUNEGARAN SURAKARTA LIBRARY - Mega Alif Marintan; Qisthi Faradina Ilma Mahanani; Salsabilla Nathania Arumsasi (2024)
Libraries have an important role in preserving local wisdom treasures. One of the libraries that is massive in carrying out this role is the Reksa Pustaka Mangkunegaran Surakarta Library. Javanese manuscripts are cultural artifacts that contain valuable knowledge that is useful in life. Based on the benefits of the manuscript for future generations and considering the age of the manuscript, it is necessary to digitize it in an effort to preserve knowledge and add to the treasures of Indonesian manuscript studies. This research aims to describe efforts to digitize ancient Javanese archives at Reksa Pustaka. The research method uses qualitative interviews with librarians, the study of related documents, and also observation. The results of the research show that efforts to digitize Javanese manuscripts are carried out by making copies in the form of digital documents so as to increase the collection with better quality and make it easily accessible to library users. The policy for digitizing ancient manuscripts includes selection, storage, and transliteration. The stages of digitizing ancient manuscripts are pre-digitization, digitization, editing, and finalization, namely checking and printing the manuscript.